Regional Disparities and Public Policies in Italy: Some Considerations in Light of a Performance Analysis - Giorgio Fazio; Davide Piacentino; Erasmo Vassallo (European Regional Science Association (ERSA), 2006)
Since the beginning of the 1990s, the Italian Government has attempted to implement a new generation of policies aimed at reducing regional disparities. It is claimed that compared to the past, these policies should be more far reaching since they emphasize the importance of the structural economic conditions in promoting growth and convergence. In this paper, we use a dataset of regional social and economic indicators in order to look at the evidence surrounding the outcome of these policies. A frontier approach seems to be suitable for the purpose of this research, as it yields a ranking of performance scores where regions can be compared in cross-sectional and a temporal dimension. Additionally to the traditional measures of economic development such as GDP per capita, we also run the analysis on competitiveness and entrepreneurship measures. Early results seem to provide interesting evidence with respect to the regional features of the development policies.
Keywords: 330